Multifunctional Hybrids Based on 2D Fluorinated Graphene Oxide and Superparamagnetic Iron Oxide Nanoparticles. (23rd October 2017) - Radhakrishnan, Sruthi; Sudeep, Parambath M.; Park, Jun Hyoung; Woellner, Cristiano F.; Maladonado, Kierstein; Galvao, Douglas S.; Kaipparettu, Benny Abraham; Tiwary, Chandra Sekhar; Ajayan, Pulickel M.
Abstract: Carbon‐based nanomaterials have garnered a lot of attention in the research of yesteryear. Here this study reports a composite based on fluorinated graphene oxide—a multifunctional subsidiary of graphene; and iron oxide nanoparticles as a contrast agent for magnetic resonance imaging (MRI). Extensive structural and functional characterization is carried out to understand composite behavior toward biotoxicity and its performance as a contrast agent. The electron withdrawing fluorine group decreases the charge transfer to iron oxide increasing the magnetic saturation of the composite thus enhancing the contrast. The interaction of paramagnetic and superparamagnetic systems yields a superior contrast agent for MRI and fluorescent imaging. Abstract : A hybrid of fluorinated graphene oxide (FGO) and iron oxide nanopartices is synthesized starting from fluorinated graphite. Owing to the magnetic contributions from fluorine, the hybrid has a higher magnetic saturation than iron oxide, due to which it gives a better magnetic resonance imaging (MRI) contrast. The fluorescent properties of FGO enable to combine fluorescent imaging with MRI contrast.